EFFECT OF BIOSTIMULANTS ON SOME BIOACTIVE COMPOUNDS AND NITRATE LEVEL IN LETTUCE (Lactuca sativa L.) GROWN UNDER UNHEATED PLASTIC TUNNEL - Yaseen, A. A.; Hajos, M. T. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
Based on the regulation (EU) No 2015/1107 in 8 July 2015, Willow (Salix alba) bark extract is a recent approved basic substance in Europe as a safe and effective environmentally friendly fungicide to be used in plant protection. Because of having indole butyric acid content, it is also used as a growth hormone to promote rooting in cutting propagation of wooden part in horticultural plants. This research aimed to evaluate the effect of willow extract and Ferbanat L (Bistep) on lettuce leaves. Bistep is an organic solution of nano fertilizer which is produced in Hungary and allowed as „Bistep plant conditioner”. Furthermore, the experiment evaluated their interaction on some bioactive compounds in different lettuce varieties, too. Three different lettuce varieties (King of May, Kobak and Great Lakes) were evaluated for total polyphenols, vitamin C and nitrate content in fresh leaves. The results indicate that the contents were significantly affected by the used biostimulants rather than varieties. Significantly difference of the total polyphenols was recorded in the plants treated with Willow + Bistep (80.64 mg GAE / 100g) in comparison to the control (55.85 mg GAE / 100g) in the mean of varieties. Similar result was recorded for the vitamin C. However, plants treated with Willow extract resulted in the highest level of nitrate content (692.00 mg/100g), while the lowest amount was measured in the control (488.00 mg/100g). According to our results, Willow bark extract can be a beneficial source of natural growth regulator or fungicide; however, when it is used alone for vegetables, the nutrient content (mainly nitrate level) must be checked before consuming and delivering to the market.